Usulan Perancangan Tata Letak Pabrik NPK 3 Menggunakan Metode Systematic Layout Planning di PT. Pupuk Kujang Cikampek - Hajjijah, Almira; Amalia, Akhsani Nur; Widarman, Agung (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. Pupuk Kujang Cikampek, as a national fertilizer producer, currently operates two NPK plants (NPK 1 and NPK 2). In 2024, the company is projected to face a demand of 165,007 tons of NPK fertilizer. If this demand remains unmet, it may lead to unfulfilled customer needs and lost market opportunities, which could negatively impact the company. Therefore, a plan to build a third NPK plant (NPK 3) is deemed necessary to meet future market demands. This study aims to design a facility layout for the NPK 3 plant using the Systematic Layout Planning (SLP) method in order to improve material flow efficiency, minimize material handling costs, and optimize space utilization. The results show that the required floor area is 1,543.48 m² for the raw material warehouse, 785 m² for the finished goods warehouse, and 465.57 m² for the production area. The proposed plant layout is designed in a linear configuration that follows the production process flow, which significantly reduces material handling costs compared to the initial layout.